Economic Analysis Of Leafy Vegetable Farming In Tawiri Village, Teluk Ambon Subdistrict, Ambon City - Vilicia jovanca lakalay; August.E. Pattiselano; J.M. Luhukay (International journal of technology and education research, 2025)
Purpose this study aims to analyze the income and feasibility of leafy vegetable farming in Tawiri Village. The vegetables analyzed include water spinach (kangkung), mustard greens (sawi), and spinach (bayam). The sample was selected purposively, consisting of 37 farmers out of a total population of 112 leafy vegetable farmers in Tawiri Village, Teluk Ambon District, Ambon City. The data used includes both primary and secondary data. Methodology the study employs income analysis, cost analysis, and farming feasibility analysis using the R/C ratio (Revenue-Cost Ratio) and comparison with land rental costs. Results the research findings show that the average income from leafy vegetable farming in Tawiri Village is Rp 2,735,972.59 per planting season, with an R/C ratio of 3.63. This means that every one rupiah of production cost generates revenue of Rp 363.000. Findings farmers in Tawiri Village cultivate a wide variety of leafy vegetables, such as water spinach, mustard greens, and spinach. Novelty this study was conducted specifically on farmers in Tawiri Village using not only income analysis but also a comprehensive feasibility assessment (including R/C ratio ). Originality the research uses recent data obtained through direct interviews and field observations. Conclusion the farmers’ income is proven to be higher than the land rental cost. Thus, leafy vegetable farming in the area is considered feasible and profitable for development.